2002
DOI: 10.1091/mbc.01-08-0399
|View full text |Cite
|
Sign up to set email alerts
|

ER-Golgi Traffic Is a Prerequisite for Efficient ER Degradation

Abstract: Protein quality control is an essential function of the endoplasmic reticulum. Misfolded proteins unable to acquire their native conformation are retained in the endoplasmic reticulum, retro-translocated back into the cytosol, and degraded via the ubiquitin-proteasome system. We show that efficient degradation of soluble malfolded proteins in yeast requires a fully competent early secretory pathway. Mutations in proteins essential for ER-Golgi protein traffic severely inhibit ER degradation of the model substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 91 publications
(115 reference statements)
4
86
0
Order By: Relevance
“…Cell Labeling and Immunoprecipitation-CPY* pulse-chase experiments were performed as described previously (42). Temperature-sensitive strains were grown at 25°C and shifted to restrictive temperature for the times indicated in the figure legends.…”
Section: Y834ementioning
confidence: 99%
See 1 more Smart Citation
“…Cell Labeling and Immunoprecipitation-CPY* pulse-chase experiments were performed as described previously (42). Temperature-sensitive strains were grown at 25°C and shifted to restrictive temperature for the times indicated in the figure legends.…”
Section: Y834ementioning
confidence: 99%
“…EndoH treatment was done as follows. Spheroplast homogenates and immunoprecipitations were done as described previously (42,43). After washing the Sepharose A-bound antigenic material with immunoprecipitation buffer (42), the Sepharose was washed once with washing buffer (50 mM potassium phosphate, pH 5.5, 0.02% SDS) and treated with 25 l of EndoH buffer (50 mM potassium phosphate pH 5.5, 0.02% SDS, 100 mM ␤-mercaptoethanol) supplemented with or without EndoH (4 milliunits).…”
Section: Y834ementioning
confidence: 99%
“…For example, the analysis of topologically distinct ERAD substrates indicates that molecular chaperones in the cytoplasm and in the ER lumen distinguish membrane and soluble substrates, respectively (Huyer et al, 2004), and which chaperones target proteins for degradation is dependent on the site of the misfolded domain (Taxis et al, 2003;Vashist and Ng, 2004; reviewed in Ahner and Brodsky, 2004). Furthermore, the proposal that ERAD substrates are retained in the ER was challenged with the elucidation of the sec-dependent ERAD pathway, in which a soluble ERAD substrate, a misfolded form of carboxypeptidase Y (CPY*), was shown to transit between the ER and Golgi before retrotranslocation and degradation (Caldwell et al, 2001;Vashist et al, 2001;Taxis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the analysis of topologically distinct ERAD substrates indicates that molecular chaperones in the cytoplasm and in the ER lumen distinguish membrane and soluble substrates, respectively (Huyer et al, 2004), and which chaperones target proteins for degradation is dependent on the site of the misfolded domain (Taxis et al, 2003;Vashist and Ng, 2004; reviewed in Ahner and Brodsky, 2004). Furthermore, the proposal that ERAD substrates are retained in the ER was challenged with the elucidation of the sec-dependent ERAD pathway, in which a soluble ERAD substrate, a misfolded form of carboxypeptidase Y (CPY*), was shown to transit between the ER and Golgi before retrotranslocation and degradation (Caldwell et al, 2001;Vashist et al, 2001;Taxis et al, 2002).Some aberrant soluble proteins in the secretory pathway may escape the ER quality control machinery and are degraded instead in the vacuole (Hong et al, 1996;Holkeri and Makarow, 1998;Jorgensen et al, 1999;Coughlan et al, 2004; reviewed in Arvan et al, 2002). Furthermore, Spear and Ng (2003) reported that the ERAD pathway can be saturated by CPY* overexpression and that excess CPY* is degraded in the vacuole after transiting through the Golgi.…”
mentioning
confidence: 99%
“…The addition of only the first three residues of the N-linked high mannose glycan motif during nascent synthesis is necessary and sufficient to stabilize the fold (Culyba et al 2011;Price et al 2011), leaving the remaining glycan structure with chemical featuresthat are amenable to management of the protein fold properties by the TPN. For example, following COPII capture for export, COPI-containing pre-Golgi and Golgi TRaCKS are thought to redirect metastable cargo to degradation by facilitating Golgi to ER recycling (Aridor et al 1995;Kimata et al 2000;Taxis et al 2002;Sifers 2010;Pan et al 2011). …”
Section: Tpn Biology and Anfinsen Compartmentsmentioning
confidence: 99%